Antimalarial-induced cardiomyopathy: a systematic review of the literature. (April 2018) - Tselios, K; Deeb, M; Gladman, D D; Harvey, P; Urowitz, M B
Background: Antimalarials (AMs) are widely used in the treatment of connective tissue diseases. Their main side effect is retinal damage, while heart disease has been described in isolated cases. The aim of this study is to systematically review the existing literature on AM-induced cardiomyopathy (AMIC). Methods: The PubMed database was searched for heart biopsy-confirmed AMIC cases. Information on demographics, clinical presentation, concomitant AM-related toxicity, cardiological investigations, treatment and outcome were collected. Descriptive statistics were used. Results: Forty-seven cases (42 females) were identified with a mean age at diagnosis 56.4 ± 12.6 and mean AM treatment duration 12.7 ± 8.2 years. Systemic lupus erythematosus ( n = 19) and rheumatoid arthritis ( n = 18) were the most common primary diseases. Clinical presentation was that of congestive heart failure in 77%, while eight patients presented with syncope (17%). Complete atrioventricular block was reported in 17 patients; 24 received a permanent pacemaker (51%). Impaired systolic function was detected in 52.8%, bi-ventricular hypertrophy in 51.4% and restrictive filling pattern of the left ventricle in 18 patients. Cardiac magnetic resonance showed late gadolinium enhancement in seven cases, with a non-vascular pattern in the interventricular septum. Cardiomyocyte vacuolation was reported in all cases; intravacuolar lamellar and curvilinear bodies were observed in 46 (98%) and 42 (89.4%) respectively. Mortality rate was 45% (18/40). Conclusion: AMIC is a rare, probably under-recognized, complication of prolonged AM treatment. It presents as a hypertrophic, restrictive cardiomyopathy with or without conduction abnormalities. Early recognition and drug withdrawal are critical with a survival rate of almost 55%.